Respon Pertumbuhan dan Produksi Labu Madu (Cucurbita moschata) Keturunan Keempat (F4) Hidroponik Sistem NFT pada Konsentrasi Nutrisi AB Mix yang Berbeda - Khoirul Anam, Muhammad; Wahyuni, Endang Sri (Program Studi Agroteknologi, 2024)
This study aims to obtain the best concentration of AB Mix nutrients for the growth and production of four (4) phenotypes of honey gourd (Cucurbita moschata) hydroponic NFT system, as well as determine the growth and production of four (4) phenotypes of honey gourd hydroponic NFT system at different AB Mix nutrient concentrations. This research was carried out at Greenhouse DnR Hydroponic Farm Housing Pondok Bedadung Indah Block AA.01. Sumbersari District, Jember Regency, East Java with an altitude of 70 meters above sea level from November 2022 to January 2023. This study was conducted using a Complete Randomized Design (RAL) factorial 3 x 4 with 3 repeats. The first factor is the concentration of AB Mix (N) nutrients consisting of three (3) levels, namely: 700 – 1400 ppm (N1), 900 - 1700 ppm (N2), 1100 - 2000 ppm (N3) and the second factor: phenotype (B) consists of four (4) phenotypes, namely: Flat round (B1), Round oval (B2), Long-necked (B3), Notched (B4). The parameters observed in this study include plant height, number of leaves, number of male flowers, number of female flowers, fruit diameter, fruit length, fruit weight, sweetness content. The observed data were analyzed with the F test to determine the effect of treatment. Different results were marked, followed by a level of 0.05. Using Duncan software test with SPSS 26 for windows. The results showed that AB Mix nutrition with a concentration of N3 (1100-2000) ppm resulted in the highest growth and production of F4 honey pumpkin on the parameters of plant height, number of leaves, number of male flowers, fruit diameter, fruit length, fruit weight, sweetness content, The influence of F4 honey pumpkin phenotype causes fruit shape diversity on the parameters of fruit diameter, fruit length, fruit weight. F4 seeds are heterozygous.